Hubungan Usia, Konsumsi Makanan dan Hygiene Mulut Dengan Gejala Tonsilitis Pada Anak di Sekolah Dasar Negeri 1 Banda Sakti Kota Lhokseumawe. - Febyola, Febby Fadya; Fardian , Nur; Putri , Baluqia Iskandar; Mauliza, Mauliza; Surayya, Rahmi (Journal of Pharmaceutical and Sciences, 2025)
Tonsillitis is an inflammation and swelling of the palatine tonsils, which is part of an upper respiratory tract infection. The World Health Organization (WHO) estimates that there are approximately 287,000 cases of tonsillitis in children under 15 years of age. In Indonesia, the prevalence of tonsillitis is reported to be 214,666 cases, or about 23%. Several factors increase the risk of developing tonsillitis, such as age, food consumption, oral hygiene, and environmental factors. This study aims to examine the relationship between age, food consumption, and oral hygiene with tonsillitis symptoms in children at SDN 1 Banda Sakti, Lhokseumawe City. This is an analytic survey with a cross-sectional design. Data were collected through questionnaires completed by 100 children, selected using a proportionate stratified random sampling technique. The results showed that the majority of respondents were between 6 and 9 years old, female, had risky food consumption habits, maintained good oral hygiene, and exhibited symptoms of tonsillitis. The Chi-square test results indicated a significant relationship between age and tonsillitis symptoms (p = 0.001), food consumption and tonsillitis symptoms (p = 0.025), and oral hygiene and tonsillitis symptoms (p = 0.026). These findings suggest a significant relationship between age, food consumption, and oral hygiene with tonsillitis symptoms in children at SDN 1 Banda Sakti, Lhokseumawe City.